Developing and Enhancing Organizational Competence for SME Digital Transformation - Abdul Raheem Y. O. AL Abdiy (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
Reason: The organization's ability to adopt new, innovative behaviors is being restricted by the new, competitive environment that progress and gradual change have created. In light of overall execution factors, SMEs must implement the following digital transformations. SMEs have certain characteristics that set them apart from large corporations. Moreover, having a prototype that is authorized to recognize, impact, and expand its computerized capabilities will help SMEs grow towards more sophisticated development. Idea/procedure/approach: A top to bottom audit of the current writing on advanced Change and hierarchical productivity accomplished inside Scopus and Web of Science to recognize other computerized difficulties confronting PME and the advanced abilities that they truly do vent developer pour y foreface.  We utilized semi-organized apparatuses to safeguard supplements and work with the investigation of metadata specialists. Results: Because Regarding this review, We've got fostered a sophisticated hierarchical skill simulation for proficiency organized that empowers SMEs to distinguish and foster the computerized capacities expected to progress organized change, refined with bits of knowledge from six counseled specialists. We have noticed the significance of authoritative learning and hierarchical information to propel the computerized change of small and medium-sized. Competent modernity /esteem: known as created designs is valuable regarding small and medium-sized administrators in understand what the beginning circumstance is, explain appear computerized holes were, along with have the option by design activities to foster the advanced abilities important to move in the direction of digital maturity coordinated.